'I have a love–hate relationship with ATLAS.ti'™: integrating qualitative data analysis software into a graduate research methods course. Issue 1 (1st January 2017) - Paulus, Trena M.; Bennett, Ann M.
Abstract : While research on teaching qualitative methods in education has increased, few studies explore teaching qualitative data analysis software within graduate-level methods courses. During 2013, we required students in several such courses to use ATLAS.ti™ as a project management tool for their assignments. By supporting students' early experiences with ATLAS.ti™, we anticipated that they might continue using the tool in their future research work. Using a case study and reflective practice approach, we reviewed course materials, including student and instructor reflections, to understand what happened when data analysis software was integrated into an advanced methods course. We identified five major themes: (1) a needed push out of their comfort zones; (2) various forms of support working together; (3) keys to motivation; (4) a new generation educating the current one and (5) use of the software beyond coursework. Implications for practice include ensuring adequate access and support for learning the software, balancing methodological and technical instruction, and creating meaningful student assignments and feedback opportunities.